2018
DOI: 10.1155/2018/9230143
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bacterial Diversity in Different Heavy Oil Wells of a Reservoir in South Oman with Alkaline pH

Abstract: The identification of potential hydrocarbon utilizing bacteria is an essential requirement in microbial enhanced oil recovery (MEOR). Molecular approaches like proteomic and genomic characterization of the isolates are replacing the traditional method of identification with systemic classification. Genotypic profiling of the isolates includes fingerprint or pattern-based technique and sequence-based technique. Understanding community structure and dynamics is essential for studying diversity profiles and is ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…When both primary and secondary recuperation techniques have been applied, it is thought that MEOR can recover up to fifty percent of the remaining oil in a pond. Metabolite production and growing bacteria to achieve this increased recovery typically include changing the physical and chemical attributes petroleum products and deposit rocks [1]. As a result, MEOR could overcome the fundamental barriers to effective oil regeneration, High crude oil stiffness, poor aquifer accessibility, and maximum oil IFTs, for example, provide flow resistance strong enough to trap the oil in the pores of the reservoir rock.…”
Section: Microbial Enhanced Oil Recovery (Meor)mentioning
confidence: 99%
See 3 more Smart Citations
“…When both primary and secondary recuperation techniques have been applied, it is thought that MEOR can recover up to fifty percent of the remaining oil in a pond. Metabolite production and growing bacteria to achieve this increased recovery typically include changing the physical and chemical attributes petroleum products and deposit rocks [1]. As a result, MEOR could overcome the fundamental barriers to effective oil regeneration, High crude oil stiffness, poor aquifer accessibility, and maximum oil IFTs, for example, provide flow resistance strong enough to trap the oil in the pores of the reservoir rock.…”
Section: Microbial Enhanced Oil Recovery (Meor)mentioning
confidence: 99%
“…Certain Bacillus strains are extremely successful because they can produce biosurfactants that promote the MEOR process in situ [8]. To stimulate microbial metabolism, nutrients, most often in the form of fermentable carbohydrates, are administered [1]. Clostridium acetobutylicum morphological and cytological alterations during the formation of acetone, butanol, and ethanol in an industrial fermentation medium were found and linked with growth and physiological changes.…”
Section: Devices and Experimental Work 21 Location Of Samples And Dia...mentioning
confidence: 99%
See 2 more Smart Citations
“…That method enhanced the recovery of the entrapped crude oil by efficiently improving the primary and secondary extraction techniques. The water injected into the oil reservoir to displace the oil did not penetrate the area with high permeability and thus circumvented most of the oil trapped here [39]. The emulsified oil droplets mobilized before were entrapped in pores with high permeability, thus forcing the flow of water through them.…”
Section: O/w Emulsionsmentioning
confidence: 99%